2015
DOI: 10.1016/j.immuni.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in the Regulation of Innate and Adaptive Immunity

Abstract: Summary Mitochondria are well appreciated for their role as biosynthetic and bioenergetic organelles. In the past two decades, mitochondria have emerged as signaling organelles that contribute critical decisions about cell proliferation, death and differentiation. Mitochondria not only sustain immune cell phenotypes but also are necessary for establishing immune cell phenotype and their function. Mitochondria can rapidly switch from primarily being catabolic organelles generating ATP to anabolic organelles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
614
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 751 publications
(658 citation statements)
references
References 125 publications
7
614
0
10
Order By: Relevance
“…Additionally and in keeping with the nutrient leveldependent activation of SIRT3 (23), 24 hours of fasting in human subjects similarly blunts inflammasome activation. Interestingly, the disruption of mitochondrial homeostasis via alternate regulatory perturbations has also been found to evoke innate immunological reactions (39,40), which, together with our data, support the emerging understanding of the intimate interaction between mitochondrial integrity and the innate immune system (41). Strategies to enhance mitochondrial integrity to ameliorate diseases have been long sought after, and the findings in this study, showing that NR can recapitulate inflammasome modulatory effects of fasting on the NLRP3 inflammasome, highlight the potential to target SIRT3 activation in NLRP3 inflammasome-linked diseases.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally and in keeping with the nutrient leveldependent activation of SIRT3 (23), 24 hours of fasting in human subjects similarly blunts inflammasome activation. Interestingly, the disruption of mitochondrial homeostasis via alternate regulatory perturbations has also been found to evoke innate immunological reactions (39,40), which, together with our data, support the emerging understanding of the intimate interaction between mitochondrial integrity and the innate immune system (41). Strategies to enhance mitochondrial integrity to ameliorate diseases have been long sought after, and the findings in this study, showing that NR can recapitulate inflammasome modulatory effects of fasting on the NLRP3 inflammasome, highlight the potential to target SIRT3 activation in NLRP3 inflammasome-linked diseases.…”
Section: Discussionsupporting
confidence: 84%
“…It was also shown that the elevation of cellular O 2˙− /H 2 O 2 was an early event during adipogenesis pointing to its potential function in serving as a co-signal for differentiation (Tormos et al, 2011). It should be emphasized at this point that cellular H 2 O 2 is well documented to play a role in cell differentiation (Weinberg et al, 2015). By knocking down Rieske iron sulfur protein (RISP), which prevents the accumulation of semiquinone and O 2˙− formation, the authors were able to show that the source of ROS was complex III of the electron transport chain (Tormos et al, 2011).…”
Section: Adipocyte Differentiationmentioning
confidence: 98%
“…Interestingly, however, we found that mLysMD3 co-localizes with GM130+ structures in human and mouse cells, consistent with localization to the Golgi (11), and that, furthermore, mLysMD3 is a type II integral membrane protein with LysM in the cytoplasm. While traditional paradigms for PAMP-sensing focus on localization of pattern recognition receptors at the cell surface, it is now appreciated that intracellular organelles such as mitochondria, the ER, and the Golgi apparatus can serve innate immune signaling platforms (43). For instance, in primary cells isolated from Drosophila infected with Wolbachia pipientis bacteria, Wolbachia can be identified in a GM130+ cellular compartment, or an immediately adjacent compartment (44).…”
Section: Significance Of Mlysmd3 Localization and Immune Functions Ofmentioning
confidence: 99%